Boron isotopes in the Huaihe River, China: An exploration of anthropogenic contamination - Chunnian Da; Jin Yu; Qinghui Huang; Linjun Wu; Peng Ji; Dukai Huang (Water Supply, 2022)
Thirty-four water samples were collected to measure their boron concentrations and δ11B values. The results indicated that the concentrations of boron in the Huaihe River ranged from 37.99 to 105.99 μg/L, much lower than those of groundwater, farmland irrigation water and sewage water. The δ11B values were between −3.12‰ and 3.21‰, with a mean value of −0.44‰. There were obvious variations trend of boron and δ11B between upstream, midstream and downstream. δ11B had a relatively high correlation with pH, boron and chlorine. Boron was positively correlated with EC, Na+, K+, F−, Li+, As and δ11B, while negatively correlated with Ca2+and Mg2+ in water. The structural equation model suggested industrial structure, population, economic development and pollution emission had positive effects on boron, whereas industrial structure and pollution emission had positive effects on δ11B. The contents of boron and δ11B showed a slight difference between the farmland, groundwater, sewage treatment plant and the Huaihe River. Hierarchical cluster analysis indicated that the same source was occurred between the Huaihe River and groundwater, between farmland and sewage treatment plant. A stable isotope analysis in R model revealed that detergent provided the greatest proportion of boron sources, followed by washing powder, municipal wastewater and contaminated groundwater. HIGHLIGHTS The different water samples were collected to determine the boron and δ11B.; The correlations between the physical and chemical parameters and boron isotopic were studied.; A structural equation model was used to analyze the effects of anthropogenic factors.; Hierarchical cluster analysis was employed to distinguish the source.; Spatial distribution characteristics of boron and boron isotope were studied.;